Numerical Analysis and Parametric Optimization of a Static Wavy Flag for Heat Transfer Enhancement (Global Journals of Research in Engineering, 2022)
This work investigates the effect of different parameters of a static wavy flag vortex generator on the heat transfer in a rectangular channel using Computational Fluid Dynamics CFD analysis This work encompasses optimizing several parameters of a flag such as flag height from the surface position in the channel number of triangular shapes in a flag and rectangular surface area of the flag Post analysis results exhibit encouraging results with average Nusselt number in flag height FH optimization exceeding that in no flag condition by 41 84 47 79 54 68 for Re 8236 12354 and 18344 respectively whereas further position optimization of FH optimized flag exceeds average Nusselt number in no flag condition by 46 86 70 68 and 87 26 for the corresponding Re With significantly less practical application of flags for heat transfer enhancement in industry this work aims to establish flags as an effective heat transfer enhancement device and demonstrate that with the right optimized parameters a significant increase of heat transfer in the channel can be achieved
Keywords: convective heat transfer; heat transfer enhancement; turbulence; vortex generator